Analysis of the Effect of Pretreatment of Empty Palm Oil Bunches (TKKS) on Biogas Production - David Manuel; Nasihin Rahman (Institute of Computer Science (IOCS), 2024)
This study investigates the effect of different pretreatment methods mechanical, chemical, and biological on biogas yield and quality from TKKS. Mechanical pretreatment involves shredding and grinding TKKS to increase surface area and enhance enzymatic accessibility, facilitating microbial degradation of cellulose and hemicellulose. Chemical pretreatment employs acid hydrolysis to disrupt lignocellulosic bonds, releasing fermentable sugars for improved substrate availability in anaerobic digestion. Biological pretreatment utilizes enzymatic or microbial processes to enhance biomass deconstruction and accelerate methane production. Experimental results demonstrate that all pretreatment methods enhance biogas production compared to untreated TKKS. Mechanical pretreatment yields significant improvements in biogas yield and methane content, owing to enhanced substrate accessibility. Chemical pretreatment shows comparable efficacy, albeit with considerations for optimal acid concentration and microbial inhibition. Biological pretreatment exhibits superior methane production rates, underscoring its potential in maximizing biogas recovery from TKKS. The implications of these findings extend to sustainability benefits, including reduced greenhouse gas emissions and enhanced waste management practices within the palm oil industry. Techno-economic feasibility and scalability considerations highlight mechanical and biological pretreatment methods as viable options for industrial-scale biogas production from TKKS.